Kaldorian cumulative causation in the euro area: An empirical assessment of divergent export competitiveness - Sascha Keil; Walter Paternesi Meloni (Hans-Böckler-Stiftung, Macroeconomic Policy Institute (IMK), Forum for Macroeconomics and Macroeconomic Policies (FMM), 2024)
Over the past decades, models of circular and cumulative causation, based on the endogenous relations between prices, exports, and labour productivity, have lost prominence in explaining economic dynamics. We argue that, in the absence of counterbalancing mechanisms, the combination of price-sensitive exports and the triggering effect of exports on productivity can enable feedback loops and can significantly shape macroeconomic reality in the short-to-medium run. We apply an adapted export-led model of cumulative causation to 10 major countries belonging the Euro area, a region characterized by divergent wage growth trajectories reflected in divergent export competitiveness and lack of equilibrating mechanisms. Specifically, the model is tested for the period 1995-2020 employing a country- level system of equations (3SLS-ARDL). Our findings indicate that for the majority of the countries examined, this feedback mechanism - comprising price-sensitive exports and export demand affecting productivity growth - exacerbates macroeconomic disparities in terms of labour productivity. While nominal wages act as a potential trigger through their impact on price competitiveness, they also serve as a central factor that retards the feedback mechanism due to the Verdoorn effect of wage-induced demand. Overall, our results affirm the significance of price-induced and export-led theories of cumulative causation while also delineating its limitations, particularly regarding price competitiveness-oriented export-led growth strategies.
Keywords: F16; F41; J30; 330; international trade; export; competitiveness; unit labour cost; wages; productivity; European imbalances